Effectiveness of Using Flash Card Learning Media in English Learning in Elementary Schools - Deysti Trifena Tarusu; Mutia Harun (Departement of Mathematics Education, 2024)
The purpose of this literature review is to determine the effectiveness of flash card media in teaching English in elementary schools. Flash cards as visual aids have been widely used in education to enhance students' understanding and information retention. Through the analysis of previous studies, this research has identified several important factors related to the use of flash cards, such as their impact on vocabulary, speaking skills, and students' motivation to learn. The research results show that flash cards can enhance student engagement in the learning process.